NITRATION OF ACETYL-1-THIAINDANES AND 1-THIOCHROMANES - Mingmikul Kurbanov; Iroda Yuldashova; Suvonkul Nurmanov (International Engineering Journal For Research & Development, 2021)
This article is aimed at studying the electrophilic gap in the aromatic part of the molecule of benzothiophene and thiochroman derivatives with nitrating agents.